‘Senior Citizen’: Ironic Depiction of West Africa’s Herder-Farmer Crisis in a Conceptual Ceramics Exposition - Jonathan Okewu; AI Chukwuma Okoli (African Journal of Inter-Multidisciplinary Studies, 2023)
This paper proffers an art-speech of the farmer-herder crisis in Nigeria from the standpoint of the conceptual ceramic’s exposition. Using the figurative construct of ‘senior citizen’ and the visual art form of conceptual ceramics, this paper creates a sort of metaphorized analogy that depicts an allegory of Nigeria’s perennial farmer-herder crisis scenario, where the wellbeing of the citizenry appears to have been subordinated to those of the herders and their herds. The uncommon ceramic art approach that negates traditional production methods has been explored in this study to interrogate the outlined concerns. This process includes the pinching of plastic clay, placing it in the palm, rolling the clay with both palms into a stick-like shape, placing the stick at the foot of the fingers, tightly compressing the clay by closing the fists, and finally releasing the clay to reveal the product. This style that has been termed fragmented clay palm press terracotta on canvas proved effective and fluid enough to achieve the essence of this study. The intriguing situation of Nigeria’s socio-political metaphor vis-à-vis the prevailing farmer-herder conundrum is explored in an attempt to foreground the existential irony that this awkward situation portends.